Bilateral NIRS measurements of muscle mitochondrial capacity: Feasibility and repeatability. Issue 8 (4th May 2021) - Hanna, Rewais; Gosalia, Jigar; Demalis, Alaina; Hobson, Zachary; McCully, Kevin K.; Irving, Brian A.; Mookerjee, Swapan; Vairo, Giampietro L.; Proctor, David N.
Abstract: Background: Non‐invasive determination of mitochondrial capacity via near infrared spectroscopy (NIRS) typically involves voluntary exercise of a single muscle group followed by as many as 26 brief ischemic cuff occlusions to determine a single recovery rate constant ( k ). Purpose: To determine the within‐ and between‐visit repeatability of a shortened bilateral NIRS protocol, and to establish the feasibility of hamstring k measurements. Methods: Sixteen young (eight women, eight men; 22 ± 3 years) active adults underwent a bilateral electrical stimulation protocol in which multiple ( n  = 4) measurements of k for the vastus lateralis (VL) and medial hamstring (MH) muscles were determined on two visits. Repeatability (CV% and intraclass correlations, ICC) and equivalency across visits were assessed for both muscles. Results: Mean k values in the VL were consistent with published values and within‐visit ICCs were moderately high for both muscles in both sexes. In men, average k values on visit 2 were within 1% (VL muscle) and 5% (MH muscle) of the values on visit 1 (all p  > 0.78). In women, average k values were 10%–15% lower on visit 2 ( p  = 0.01 and p  = 0.15 for MH and VL) with the largest between‐visit differences in a subset of participants with the most days between visits. Conclusions: This bilateral NIRS protocol is time efficient and provides valid estimates of k in both sexes and muscle groups with acceptable within‐visit repeatability. Lower than expected between‐visit repeatability in some participants reinforces the need for further investigation of this newly developed protocol to identify and control for experimental and behavioral sources of variation. Abstract : We developed and tested the reliability of a novel bilateral near infrared spectroscopy protocol to estimate mitochondrial capacity ( k ) in the vastus lateralis and hamstring muscles of active younger men and women. Within‐visit intraclass correlations were moderately high, but between‐visit repeatability of k in these muscles was lower than expected in a subset of women. Bilateral estimates of k are feasible and time efficient even in the hamstring muscles, but further studies employing this protocol will be needed to identify sources of variation between days.